Divergent Residues Within Histone H3 Dictate a Unique Chromatin Structure in Saccharomyces cerevisiae. Issue 1 (29th October 2015) - McBurney, Kristina L; Leung, Andrew; Choi, Jennifer K; Martin, Benjamin J E; Irwin, Nicholas A T; Bartke, Till; Nelson, Christopher J; Howe, LeAnn J
Abstract: Histones are among the most conserved proteins known, but organismal differences do exist. In this study, we examined the contribution that divergent amino acids within histone H3 make to cell growth and chromatin structure in Saccharomyces cerevisiae . We show that, while amino acids that define histone H3.3 are dispensable for yeast growth, substitution of residues within the histone H3 α3 helix with human counterparts results in a severe growth defect. Mutations within this domain also result in altered nucleosome positioning, both in vivo and in vitro, which is accompanied by increased preference for nucleosome-favoring sequences. These results suggest that divergent amino acids within the histone H3 α3 helix play organismal roles in defining chromatin structure.